Biochemical and Genetic Responses of Tea (Camellia sinensis (L.) Kuntze) Microplants under Mannitol-Induced Osmotic Stress In Vitro - Lidiia Samarina; Alexandra Matskiv; Taisiya Simonyan; Natalia Koninskaya; Valentina Malyarovskaya; Maya Gvasaliya; Lyudmila Malyukova; Gregory Tsaturyan; Alfiya Mytdyeva; Marcos Edel Martinez-Montero; Ravish Choudhary; Alexey Ryndin (Plants, 2020)
Osmotic stress is a major factor reducing the growth and yield of many horticultural crops worldwide. To reveal reliable markers of tolerant genotypes, we need a comprehensive understanding of the responsive mechanisms in crops. In vitro stress induction can be an efficient tool to study the mechanisms of responses in plants to help gain a better understanding of the physiological and genetic responses of plant tissues against each stress factor. In the present study, the osmotic stress was induced by addition of mannitol into the culture media to reveal biochemical and genetic responses of tea microplants. The contents of proline, threonine, epigallocatechin, and epigallocatechin gallate were increased in leaves during mannitol treatment. The expression level of several genes, namely DHN2, LOX1, LOX6, BAM, SUS1, TPS11, RS1, RS2, and SnRK1.3, was elevated by 2–10 times under mannitol-induced osmotic stress, while the expression of many other stress-related genes was not changed significantly. Surprisingly, down-regulation of the following genes, viz. bHLH12, bHLH7, bHLH21, bHLH43, CBF1, WRKY2, SWEET1, SWEET2, SWEET3, INV5, and LOX7, was observed. During this study, two major groups of highly correlated genes were observed. The first group included seven genes, namely CBF1, DHN3, HXK2,SnRK1.1, SPS, SWEET3, and SWEET1. The second group comprised eight genes, viz. DHN2, SnRK1.3, HXK3, RS1, RS2,LOX6, SUS4, and BAM5. A high level of correlation indicates the high strength connection of the genes which can be co-expressed or can be linked to the joint regulons. The present study demonstrates that tea plants develop several adaptations to cope under osmotic stress in vitro; however, some important stress-related genes were silent or downregulated in microplants.